Development of Media Game on Acid-Base Material and Its Effect on Self-Regulated Learning - Rifki, Ikfisani Yuniar; Lutfi, Achmad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aimed to obtain an Android-based chemistry racing challenge game as a learning media for acid-base materials that are valid, practical, and effective to facilitate students’ self-regulated learning. The research method used is research and development (R&D). The instruments used are validation sheets, student response questionnaire sheets, self-regulated learning questionnaire sheets, and test question sheets. The research subjects were 18 students of SMA Muhammadiyah 2 Sidoarjo. The validation results get a score mode of â‰¥ 3 with a good category. The practicality test scored â‰¥ 61% for each goal with a very practical category. The effectiveness of games as learning media is seen from student learning outcomes and self-regulated learning. The classical completeness achieved is 61%, and students’ self-regulated learning achievedÂ â‰¥ 80.1% with a very good category. Thus, it can be concluded that the Chemistry Racing Challenge game is valid, practical and effective as a game learning media.